High-resolution longitudinal N- and O-glycoprofiling of human monocyte-to-macrophage transition. (9th March 2020) - Hinneburg, Hannes; Pedersen, Jessica L; Bokil, Nilesh J; Pralow, Alexander; Schirmeister, Falko; Kawahara, Rebeca; Rapp, Erdmann; Saunders, Bernadette M; Thaysen-Andersen, Morten
Abstract: Protein glycosylation impacts the development and function of innate immune cells. The glycophenotypes and the glycan remodelling associated with the maturation of macrophages from monocytic precursor populations remain incompletely described. Herein, label-free porous graphitised carbon–liquid chromatography–tandem mass spectrometry (PGC-LC-MS/MS) was employed to profile with high resolution the N - and O -glycome associated with human monocyte-to-macrophage transition. Primary blood-derived CD14 + monocytes were differentiated ex vivo in the absence of strong anti- and proinflammatory stimuli using a conventional 7-day granulocyte-macrophage colony-stimulating factor differentiation protocol with longitudinal sampling. Morphology and protein expression monitored by light microscopy and proteomics validated the maturation process. Glycomics demonstrated that monocytes and macrophages display similar N -glycome profiles, comprising predominantly paucimannosidic (Man1-3 GlcNAc2 Fuc0–1, 22.1–30.8%), oligomannosidic (Man5-9 GlcNAc2, 29.8–35.7%) and α2, 3/6-sialylated complex-type N -glycans with variable core fucosylation (27.6–39.1%). Glycopeptide analysis validated conjugation of these glycans to human proteins, while quantitative proteomics monitored the glycoenzyme expression levels during macrophage differentiation. Significant interperson glycome variations were observed suggesting a considerable physiology-dependent or heritable heterogeneity of CD14 + monocytes. Only few N -glycome changes correlated with the monocyte-to-macrophage transition across donors including decreased core fucosylation and reduced expression of mannose-terminating (paucimannosidic-/oligomannosidic-type) N -glycans in macrophages, while lectin flow cytometry indicated that more dramatic cell surface glycan remodelling occurs during maturation. The less heterogeneous core 1-rich O -glycome showed a minor decrease in core 2-type O -glycosylation but otherwise remained unchanged with macrophage maturation. This high-resolution glycome map underpinning normal monocyte-to-macrophage transition, the most detailed to date, aids our understanding of the molecular makeup pertaining to two vital innate immune cell types and forms an important reference for future glycoimmunological studies.